Seroprevalence of bovine brucellosis in Puerto Inca district, Huánuco - Meza C., Alan (2010)
The aim of the present work was to estimate the seroprevalence of bovine brucellosis in cattle reared under an extensive breeding system in the district of Puerto Inca, Huánuco, Peru in 2007. Blood samples were collected (n=3321) for the diagnosis of Brucella spp. by the Rose Bengal agglutination test. None of the samples resulted positive and the prevalence showed by the @Risk stochastic simulations software was 0.031% with ranges of 0.0008 and 0.1144%. The low prevalence would allow the implementation of a program to eradicate bovine brucellosis in the district of Puerto Inca.